2013
DOI: 10.1016/j.aquatox.2013.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Molecular responses to toxicological stressors: Profiling microRNAs in wild Atlantic salmon (Salmo salar) exposed to acidic aluminum-rich water

Abstract: Atlantic salmon (Salmo salar) is among the most sensitive organisms toward acidic, aluminum exposure. Main documented responses to this type of stress are a combination of hypoxia and loss of blood plasma ions. Physiological responses to stress in fish are often grouped into primary, secondary and tertiary responses, where the above mentioned effects are secondary responses, while primary responses include endocrine changes as measurable levels of catecholamines and corticosteroids. In this study we have expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 69 publications
1
18
0
Order By: Relevance
“…These ncRNAs can be broadly classified as either long ncRNAs (lncRNAs; > 200 nucleotides) or small RNAs (sRNAs; < 200 nucleotides). More than 550 distinct long intervening noncoding RNAs (lincRNAs, one type of lncRNAs) were identified in zebrafish embryo (Ulitsky et al, 2011); 224 unique mature microRNAs (miRNAs, one type of sRNAs) were identified in Atlantic salmon (Salmo salar) (Kure et al, 2013). These newly discovered transcripts will facilitate the annotation of sequenced genome and lay the ground for future functional studies.…”
Section: Novel Transcript Discoverymentioning
confidence: 99%
See 1 more Smart Citation
“…These ncRNAs can be broadly classified as either long ncRNAs (lncRNAs; > 200 nucleotides) or small RNAs (sRNAs; < 200 nucleotides). More than 550 distinct long intervening noncoding RNAs (lincRNAs, one type of lncRNAs) were identified in zebrafish embryo (Ulitsky et al, 2011); 224 unique mature microRNAs (miRNAs, one type of sRNAs) were identified in Atlantic salmon (Salmo salar) (Kure et al, 2013). These newly discovered transcripts will facilitate the annotation of sequenced genome and lay the ground for future functional studies.…”
Section: Novel Transcript Discoverymentioning
confidence: 99%
“…Of the 145,394 genes detected by RNA-seq, 325 genes were significantly upregulated, while 349 genes were significantly downregulated, and these differentially expressed genes were found to be implicated in neurobehavioral defects, mitochondrial dysfunction and the metabolisms of proteins and fats. In a most recent study, RNA-seq was used to identify miRNAs in Atlantic salmon muscle tissue as potential biomarkers of toxicological stress (Kure et al, 2013). A total of 18 miRNAs were significantly differentially expressed in response to acidic aluminum-rich water, 4 downregulated and 14 upregulated.…”
Section: Quantifying Transcript Levelmentioning
confidence: 99%
“…However, expression of miRNAs is tissue-specific (Lagos-Quintana et al, 2002; Wienholds et al, 2005), and the zebrafish mi As have been curated from 11 tissues, whereas samples in this study were exclusive to killifish gill. A recent study reported 224 miRNAs in Atlantic salmon ( Salmo salar) blood, while the miRbase database lists 371 Atlantic salmon miRNAs, representing at least 11 tissues (Kozomara and Griffiths-Jones, 2014; Kure et al, 2013). More miRNAs have been identified in Atlantic cod ( Gadus morhua ), which has 401 miRNAs from at least nine tissues in miRBase (Andreassen et al, 2016; Kozomara and Griffiths-Jones, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…As well documented by Barton (), many scientists have divided physical, chemical, and other perceived stressors on fish into three groups: primary responses including a number of hormonal changes, particularly those in circulating levels of cortisol and catecholamines; secondary endocrine responses (directly or indirectly), as changes in blood glucose, lactate, and major ions as sodium (Na + ) and chloride (Cl − ), and tissue levels of glycogen and heat shock or stress proteins (HSPs), all of which relate to physiological adjustments such as in metabolism and respiration; tertiary responses such as changes in growth, disease resistance, and behavior may be direct or indirect consequences of primary and secondary responses. And miRNAs have the potential as high‐resolution molecular tools for studying initial primary stress responses (Kure et al, ). So the different responses of miRNAs to chemicals emphasize their possible roles as potential biomarkers in early phases of toxicological outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…So the different responses of miRNAs to chemicals emphasize their possible roles as potential biomarkers in early phases of toxicological outcomes. Kure et al () found that 18 miRNAs were significantly differentially expressed when wild Atlantic salmon were exposed to acidic aluminum‐rich water. Hu et al () studied the expression pattern of brain‐ and muscle‐specific miRNAs and concluded that miR‐124a and miR‐133a are involved in sodium thiosulfate‐induced developmental toxicity in zebrafish.…”
Section: Introductionmentioning
confidence: 99%